Ground Penetrating Radar for the Exploration of Complex Mining Contexts - Sáez Blázquez, Cristina; Maté-González, Miguel Ángel; Camargo Vargas, Sergio Alejandro; Martín Nieto, Ignacio; Protonotarios, Vasileios; González-Aguilera, Diego (Remote sensing (Basel, Switzerland), 2025)
Mining waste management is a significant environmental challenge that requires effective technical and economic solutions. In this context, the use of underground storage systems is sometimes a viable option to isolate this type of mining waste from the outside (especially when it poses a risk of environmental contamination). Despite the applicability and advantages of these structures, it is crucial to conduct thorough monitoring of the isolation and containment measures implemented during their construction. This study demonstrates how ground penetrating radar techniques can provide valuable insights into subsurface insulation layers with the aim of detecting potential water accumulation at depth and verifying the integrity of the seal and the state of buried materials. The results of the georadar survey applied on a mining case study demarcate the areas that should receive more attention in the near future and contribute to defining the most urgent actions to be implemented at the mining site. Beyond the evaluation of the 2D profiles, the research culminates in the creation of a 3D visualization tool for the entire mining site and its insulation layer, enabling users to inspect the structure’s condition at any location and obtain accurate depth measurements.